Aspects of asymmetry in Czech-Slovak biliteracy: The post-1989 context - Jana Pátková (Slovenska Literatura)
The study focuses on analysing the asymmetrical relationship between two distinct yet closely connected literary systems. The problem areas of Czech-Slovak biliteracy after 1989 include, for example, the work of the so-called dual authors and their incorporation into the literary context, Slovak literature emerging in Prague, and forms of cultural transfer as evidence of intercultural communication. The study presents the current state of research on the biliteracy of the literary field up to 1989 and then innovatively extends the scope to the situation after 1993, after the division of the common state, when the historically defined intercultural dialogue from earlier periods was replaced by a new type of communication. Although the conditions for the emergence of biculturalism were no longer part of cultural politics, examples of bicultural authors exist in both Czech and Slovak literature (Egon Bondy, Fedor Gál, Ľubomír Feldek). The forms of cultural transfer are important in both directions, albeit with typological differences. The transfer of the discussion of freedom of speech to the Czech space is of a different type than the cultural transfer in the work of Peter Karvaš and Ján Števček or, in the opposite direction, the case of the transfer of mythical narratives from Czech literature to contemporary Slovak prose.